Thermal anomaly and water origin in Weebubbie Cave, Nullarbor Karst Plain, Australia - Buzzacott, Peter; Skrzypek, G. (2021)
Study region: The Nullarbor is one of the largest contiguous karst plains in the world. Despite the absence of surface relict karst features and arid climate, the subterranean flooded cave systems are among the largest in the world. The cave waters are usually brackish and their temperatures vary over a large range (18.6–23.7 °C) suggesting potential input of warm groundwater to some of the caves. The studied Weebubbie Cave of total length ∼500 m penetrates to ∼140 m below ground and ∼40 m below sea level. Study focus: Temperature loggers were deployed in the water at various depths and distances from the entry lake to detect potential warm water inputs in three different years. The stable hydrogen, oxygen, and carbon isotope compositions of water have been analysed to detect potential hydrochemical differences in inflowing water and to investigate the origin of the cave water. New hydrological insights for the region: The thermal irregularity at the Air Dome of Weebubbie with water temperatures 0.9 °C higher than in all other cave sections, confirms some heat transfer or an inflow of warmer water. The stable isotope results suggest the cave water originates from partially evaporated (up to <20 %) modern infrequent large precipitation events. Despite the relatively high salinity (23.3 mS cm−1) of the cave water, water hydrochemistry and stable isotope composition suggest that direct large ocean water contribution to the cave is unlikely.